A Large Collection of Novel Nematode-Infecting Microsporidia and Their Diverse Interactions with Caenorhabditis elegans and Other Related Nematodes. - Gaotian Zhang; Martin Sachse; Marie-Christine Prevost; Robert J Luallen; Emily R Troemel; Marie-Anne Félix (PLoS Pathogens, 2016)
Microsporidia are fungi-related intracellular pathogens that may infect virtually all animals, but are poorly understood. The nematode Caenorhabditis elegans has recently become a model host for studying microsporidia through the identification of its natural microsporidian pathogen Nematocida parisii. However, it was unclear how widespread and diverse microsporidia infections are in C. elegans or other related nematodes in the wild. Here we describe the isolation and culture of 47 nematodes with microsporidian infections. N. parisii is found to be the most common microsporidia infecting C. elegans in the wild. In addition, we further describe and name six new species in the Nematocida genus. Our sampling and phylogenetic analysis further identify two subclades that are genetically distinct from Nematocida, and we name them Enteropsectra and Pancytospora. Interestingly, unlike Nematocida, these two genera belong to the main clade of microsporidia that includes human pathogens. All of these microsporidia are horizontally transmitted and most specifically infect intestinal cells, except Pancytospora epiphaga that replicates mostly in the epidermis of its Caenorhabditis host. At the subcellular level in the infected host cell, spores of the novel genus Enteropsectra show a characteristic apical distribution and exit via budding off of the plasma membrane, instead of exiting via exocytosis as spores of Nematocida. Host specificity is broad for some microsporidia, narrow for others: indeed, some microsporidia can infect Oscheius tipulae but not its sister species Oscheius sp. 3, and conversely some microsporidia found infecting Oscheius sp. 3 do not infect O. tipulae. We also show that N. ausubeli fails to strongly induce in C. elegans the transcription of genes that are induced by other Nematocida species, suggesting it has evolved mechanisms to prevent induction of this host response. Altogether, these newly isolated species illustrate the diversity and ubiquity of microsporidian infections in nematodes, and provide a rich resource to investigate host-parasite coevolution in tractable nematode hosts.